2020
DOI: 10.1177/1464884920965783
|View full text |Cite
|
Sign up to set email alerts
|

Trauma exposure and post-traumatic stress disorder among regional journalists in Pakistan

Abstract: This study sought to examine work-related exposure to trauma and predictors of Post-Traumatic Stress Disorder (PTSD) symptoms among regional journalists in the Khyber Pakhtunkhwa (KP) province, a conflict-ridden area in northwest Pakistan. We recruited 216 KP journalists. Analysis of the surveys revealed a high prevalence of trauma exposure and PTSD symptoms. All of the participants had covered at least one trauma inducing event. Exposure to work-related trauma, active emotional coping and avoidant emotional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…They have identified problems faced by journalists while reporting traumatic events and their effects on the audiences. Some have found that news coverage of traumatic events has horrific effects on the audience who watch television and read newspapers (Ananthan, 2017;Lee, Ha, & Pae, 2018;MacDonald & Fox, 2018;Seely, 2019;Shah et al, 2020;Smith, Drevo, & Newman, 2018). Journalists, therefore, must continually make decisions on the use of images of the traumatic event, they suggest.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…They have identified problems faced by journalists while reporting traumatic events and their effects on the audiences. Some have found that news coverage of traumatic events has horrific effects on the audience who watch television and read newspapers (Ananthan, 2017;Lee, Ha, & Pae, 2018;MacDonald & Fox, 2018;Seely, 2019;Shah et al, 2020;Smith, Drevo, & Newman, 2018). Journalists, therefore, must continually make decisions on the use of images of the traumatic event, they suggest.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Journalists, including reporters, photographers, editors and news crew, cover tragic and violent events as part of their profession. These include war, terrorist attacks, and natural calamities (Ashraf & Jan, 2018;Shah et al, 2020). Media researchers have different opinions on what type of information journalists should include in the coverage of violent events (Barnes, 2016;Dworznik, 2006;Ellwood, 2015;Massé, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Shah et al (2020) highlight the severity of the impact of trauma on regional journalists in Pakistan. Exposure to work-related trauma, active emotional coping, and avoidant emotional coping were statistically significant factors associated with PTSD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In a sample of newspaper journalists in the United States, Pyevich et al (2003) found that 61.8% of participants had been threatened verbally, 6.1% had been injured, and 5.3% had been physically assaulted while covering a story. In Pakistan's Khyber-Pakthoonkhwa province, Shah et al (2020) found that 59.3% of surveyed journalists indicated that they had been verbally threatened on the job (Shah et al, 2020).…”
mentioning
confidence: 99%